Penerjemahan Klausa Pasif dari Bahasa Inggris ke Bahasa Indonesia: Analisis Isi Novel The Fault in Our Stars Karya John Green dan Terjemahannya oleh Ingrid Dwijani Nimpoeno - Ummy Hani (Indonesian Journal of Applied Linguistics Review, 2016)
The purpose of this study is to obtain an overall view of translation of passive clause from English to Bahasa Indonesia. This study used a qualitative approach using a content analysis method. The data used in this study is passive clause, including translation equivalence, translation accuracy, translation strategies and translation error. The data source in this study is The Fault in our Stars novel by John Green in English as the source text, and the translation in Bahasa Indonesia as the target text translated by Ingrid Dwijani Nimpoeno. The findings of this study show the following: First, the passive clauses found are as many as 149 data, and as many as 118 data are formal equivalence and 22 data are textual equivalence. Second, the translation accuracy found are 140 data accurate and 9 data inaccurate. Third, there are 10 strategies found and used by translators: literal translation 86 data, transposition 24 data, modulation 21 data, naturalization 8 data, cuplet 4 data, transference 2 data, translation by a more general word 1 data, translation by a more specific word 1 data, paraphrasing 1 data, and descriptive 1 data. Fourth, the translation error found are deviation of meaning 4 data and modification of meaning 5 data.